2011
DOI: 10.1007/s12288-011-0056-4
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Anemia in Elderly: A Hospital Based Study in South India

Abstract: Anemia is a common concern in older people and can have significant morbidity and mortality. Because anemia is a sign, not a diagnosis, an evaluation is almost always warranted to identify the underlying cause. The purpose of this study was to study the clinical profile of elderly patients with anemia and to study characteristics of hematological types of anemia in such patients as well as the closest possible etiological profile. Hundred patients above the age of 60 years were included in the study. Clinical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
27
4
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(44 citation statements)
references
References 17 publications
11
27
4
2
Order By: Relevance
“…The most common pattern of anemia in their study has been found to be normocytic anemia amounting to 93.5% and 3.5% of them being microcytic, and 3% were macrocytic anemias. 3,5 In the present study, percentage of anemia in males was 64.74% and in females 70.58%. All the types of anemia based on peripheral smear were evident, normocytic being the commonest constituting 78.86%, followed by microcytic hypochromic 11.11%, macrocytic 5.96% and dimorphic 4.07%.…”
Section: Discussionsupporting
confidence: 48%
See 1 more Smart Citation
“…The most common pattern of anemia in their study has been found to be normocytic anemia amounting to 93.5% and 3.5% of them being microcytic, and 3% were macrocytic anemias. 3,5 In the present study, percentage of anemia in males was 64.74% and in females 70.58%. All the types of anemia based on peripheral smear were evident, normocytic being the commonest constituting 78.86%, followed by microcytic hypochromic 11.11%, macrocytic 5.96% and dimorphic 4.07%.…”
Section: Discussionsupporting
confidence: 48%
“…In the geriatrics age group usually patient present with common symptoms like fatigue, weakness and shortness of breath, that's why in geriatric age group anemia is usually ignored by the physicians. 3,4 According to world health organization criteria, level of hemoglobin less than 13 g/dl in case of males and less than 12 g/dl in females are considered as anemic. Hence it is necessary to study the various pattern of anemia in the elderly population.…”
Section: Introductionmentioning
confidence: 99%
“…Determining the patterns of anaemia with its changes in the RBC parameters could have important diagnostic and therapeutic implications for addressing this common problem in the adult and geriatric population. [8,9,10,11] Despite the high prevalence, very less database regarding anaemia >45 years is available in South India. [3] This prompted us to study the morphological pattern and prevalence of anaemia in a tertiary care hospital at Pondicherry.…”
Section: Introductionmentioning
confidence: 99%
“…3 Studies have shown that anemia is an independent risk factors for increase in morbidity and mortality. 4,5 Stuides have also reported association between anemia and worsening of cognition and quality of life in elderly population.…”
mentioning
confidence: 99%